Ownership Concentration and Share Valuation: Evidence from Germany - Jeremy Edwards; Alfons Weichenrieder (Center for Economic Studies and ifo Institute (CESifo), 1999)
Concentrated ownership of large listed companies is widespread throughout the world, and Germany is typical in this respect. This paper proposes a method of distinguishing empirically between the beneficial and harmful effects of ownership concentration, and applies it to German data. The results show that, for most types of largest shareholder, the beneficial effects on minority shareholders of increased ownership (greater monitoring of management, and reduced incentives to exploit minority shareholders due to greater cash-flow rights) outweigh the harmful effect (greater private benefits of control due to greater control rights).
Keywords: 330; Ownership structure; firm performance